论新加坡街名及其译名的历时演变 = A study of the diachronic development of Singapore street names and their transliterations - 陈秀君 Chin, Siew Chien (2011)
街名及其译名不仅是指涉街道的单位，也是历史渊源及文化背景的定位。在新加坡街名更反映到多语环境下，翻译结构及语言符号的确立及发展。本文尝试总结马来文—华文街名和译名的发展概况、马来文街道的变迁消长及街名特色。另外，本文以《新加坡街道指南》和相关街名录所罗列的中巫对照街名及译名为准，以比较研究的方法论述1970年代前、后二阶段马来文—华文街名及译名的演变。通过语音、书写形式与语文结构三方面的分析，探讨注音现象、通译字词的选用、意译结构、语文混用的模式及译名的规律关系，借以梳理本土性的语言背景，掌握语言文化的发展脉络，作为本土研究中多一项学术的积累。笼统来说，1970年后的街名及译名普遍是以汉语拼音及音位为注音单位、修订方言字与地域字、选用简易字及较正面或中性色彩的通译字词，并采用相对自觉的意译形式、双语或多语混用的模式和译名间同音同字或音近同字的规律结构。Street names and their transliterations do not only refer to streets and roads, but also reflect their histories and cultural contexts. Moreover, street names in Singapore establish and develop the translation structures and linguistic symbols in a multi-lingual society. This thesis tries to summarize the development trend of “Malay-Mandarin” street names and their transliterations, the changes of increase or decrease of “Malay” streets and the characteristics among all “Malay” street names. According to different editions of “Singapore Street Directory” before and after 1970, this paper also discusses the evolution of “Malay-Mandarin” street names and their transliterations by analyzing the phonetic notations, selections of Chinese characters, translation structures, features of code-mixing, and also relationships of regular patterns among all transliteration names. As addition to the native place studies research, this paper aims to generalize the background of aboriginality language and grasps the development trend of cultural language.